A Survivable Internet of Things Scheme - Omar Alhazmi, (Journal of Advanced Research in Computing and Applications, 2023)
Availability is an essential property of information systems, especially in critical infrastructure and revenue-generating systems. Availability can be compromised when an incident or an attack causes a system to shut down. Then, recovery can be applied to restore availability. One other way to achieve high availability is to start with building survivable systems. Survivable systems resist shutting down as they are built to continue operation despite being affected by incidents. Survivability depends on many factors including architecture and redundancy. Internet of Things systems are complex and often widespread, and to ensure survivability certain measures should be in place to face the challenges inherent in the nature of these systems. In this work, we preview some of the well-known IoT architectures and propose architectural schemes to ensure survivability.